A one-step, cost-effective green method to in situ fabricate Ni(OH)2 hexagonal platelets on Ni foam as binder-free supercapacitor electrode materials. Issue 5 (12th November 2014) - Li, Lingjie; Xu, Jing; Lei, Jinglei; Zhang, Jie; McLarnon, Frank; Wei, Zidong; Li, Nianbing; Pan, Fusheng
Abstract : The Ni(OH)2 hexagonal platelets were in situ fabricated on Ni foam as a binder-free supercapacitor electrode material with high performance and excellent cycling stability by a one-step, cost-effective, green hydrothermal treatment of three-dimensional (3D) Ni foam in a 15 wt% H2 O2 aqueous solution. Abstract : Nickel hydroxide (Ni(OH)2 ) is considered to be a promising alternative to the expensive and toxic RuO2 electrode material for high-performance supercapacitors; however, the fabrication method and electrochemical performance of suitable Ni(OH)2 structures are unsatisfactory. In the present work, a facile, cost-effective green method is developed to in situ fabricate Ni(OH)2 hexagonal platelets on Ni foam as a binder-free supercapacitor electrode with high performance. The Ni(OH)2 hexagonal platelets are self-grown on three-dimensional (3D) Ni foam by a one-step hydrothermal treatment of Ni foam in a 15 wt% H2 O2 aqueous solution without the use of nickel salts, acids, bases, or post-treatments. The as-prepared Ni(OH)2 hexagonal platelets-Ni foam (HNF) electrode can be used directly as a supercapacitor electrode material, thereby avoiding the need for binders and conducting agents. The Ni(OH)2 hexagonal platelets demonstrate high capacitance (2534 F g −1 at a scan rate of 1 mV s −1 ) and excellent cycling stability (97% capacitance retention after 2000 cycles at a scan rate of 50 mV s −1 ). The fabrication method developed here has the significant advantage of low-cost, facile, green, and additive-free processing, and it is therefore a promising route for preparing self-supported metal (hydr)oxide electrodes for high-performance supercapacitors and other energy-storage devices.